2021
DOI: 10.1093/cid/ciab936
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Adults After Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection and Coronavirus Disease 2019 (COVID-19) Vaccination

Abstract: Background Multisystem inflammatory syndrome in adults (MIS-A) was reported in association with the COVID-19 pandemic. MIS-A was included in the list of adverse events to be monitored as part of the emergency use authorizations issued for COVID-19 vaccines. Methods Reports of MIS-A patients received by the Centers for Disease Control and Prevention (CDC) after COVID-19 vaccines became available were assessed. Data collected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 17 publications
8
54
0
Order By: Relevance
“…Multisystem inflammatory syndrome in adults was not reported in clinical trials of COVID-19 vaccines used in the USA, and MIS-C was not observed in the 46 000 individuals aged 16 years or older who participated in safety clinical trials for BNT162b2. 10 , 25 Globally, MIS-C in individuals who had received a COVID-19 vaccine has been described in detail in the literature for eight individuals younger than 21 years, 22 , 26 , 27 , 28 , 29 , 30 , 31 excluding aggregate counts from larger analyses assessing the effect of vaccination on preventing MIS-C. 32 , 33 From the USA, two reports included three cases that are also in our surveillance results, 22 , 26 and one report described a 14-year-old child with evidence of previous SARS-CoV-2 infection (positive anti-nucleocapsid antibody test) with MIS-C onset 2 months after a second dose with BNT162b2. 31 From outside the USA, we found reports of two individuals without evidence of previous or recent SARS-CoV-2 infection and who tested negative for anti-nucleocapsid antibodies: from Denmark, a 17-year-old with MIS-C onset 5 days after dose two of BNT162b2; 28 and from Turkey, a 12-year-old with onset 27 days after dose one of BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
“…Multisystem inflammatory syndrome in adults was not reported in clinical trials of COVID-19 vaccines used in the USA, and MIS-C was not observed in the 46 000 individuals aged 16 years or older who participated in safety clinical trials for BNT162b2. 10 , 25 Globally, MIS-C in individuals who had received a COVID-19 vaccine has been described in detail in the literature for eight individuals younger than 21 years, 22 , 26 , 27 , 28 , 29 , 30 , 31 excluding aggregate counts from larger analyses assessing the effect of vaccination on preventing MIS-C. 32 , 33 From the USA, two reports included three cases that are also in our surveillance results, 22 , 26 and one report described a 14-year-old child with evidence of previous SARS-CoV-2 infection (positive anti-nucleocapsid antibody test) with MIS-C onset 2 months after a second dose with BNT162b2. 31 From outside the USA, we found reports of two individuals without evidence of previous or recent SARS-CoV-2 infection and who tested negative for anti-nucleocapsid antibodies: from Denmark, a 17-year-old with MIS-C onset 5 days after dose two of BNT162b2; 28 and from Turkey, a 12-year-old with onset 27 days after dose one of BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
“…29 Several adults have also been reported with MIS-A following COVID-19 vaccination, most of whom had evidence of previous SARS-CoV-2 infection. 23,26 This investigation highlights the challenges of diagnosing MIS-C and importance of a thorough clinical evaluation. While the CDC MIS-C case definition can be met with any type of SARS-CoV-2 antibody test (anti-spike, anti-nucleocapsid, or undifferentiated), testing for anti-nucleocapsid antibody in persons with suspected MIS-C after COVID-19 vaccination may differentiate between vaccine-versus infection-derived antibody.…”
Section: Discussionmentioning
confidence: 94%
“…Neither MIS-C nor multisystem inflammatory syndrome in adults (MIS-A) was reported in the clinical trials of COVID-19 vaccines used in the United States. 14,26 Globally, MIS-C following COVID-19 vaccination has been reported in the literature for six persons <21 years of age. 23,[27][28][29][30] Two of these persons are from the United States and are included in our case series; both had evidence of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although MIS-C seems a post-infectious severe event arising from a dysregulated immune response leading to a hyperinflammatory state, its pathogenesis is not completely elucidated. Different theories have been formulated to explain its outbreak during the pandemic, including the role of molecular mimicry, superantigen-dependent immune activation, delayed interferon response, presence of anti-interferon autoantibodies, dysregulation of the inflammasome by an extensive innate immune response primed by Toll-like Receptors expressed on ACE + type II pneumocytes, antibody-dependent enhancement, and others ( 11 13 ). Specific molecular signatures have been evidenced in MIS-C patients, highlighting the role of type II interferon and NF-κB activation in its pathogenesis ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only rare cases of multisystem inflammatory syndrome directly triggered by SARS-CoV-2 vaccination have been reported in adults and adolescents ( 13 , 17 19 ). Also the reports of classical case of MIS-C (triggered by SARS-CoV-2 exposure) in vaccinated patients are of extreme rarity.…”
Section: Discussionmentioning
confidence: 99%